Memristors using solution-based IGZO nanoparticles - Rosa, Jose (2018)
Solution-based indium-gallium-zinc oldde (IGZO) nanoparticles deposited by spin coating have been investigated as a resistive switching layer in metal-insulator-metal structures for nonvolatile memory applications. Optimized devices show a bipolar resistive switching behavior, low programming voltages of +/- 1 V, on/off ratios higher than 10, high endurance, and a retention time of up to 104 s. The better performing devices were achieved with annealing temperatures of 200 degrees C and using asymmetric electrode materials of titanium and silver. The physics behind the improved switching properties of the devices is discussed in terms of the oxygen deficiency of IGZO. Temperature analysis of the conductance states revealed a nonmetallic filamentary conduction. The presented devices are potential candidates for the integration of memory functionality into low-cost System-on-Panel technology.